Probing Ligand-Receptor Interaction in Living Cells Using Force Measurements With Optical Tweezers - Riesenberg, Carolin; Iriarte-Valdez, Christian Alejandro; Becker, Annegret; Dienerowitz, Maria; Heisterkamp, Alexander; Ngezahayo, Anaclet; Torres-Mapa, Maria Leilani (Frontiers in Bioengineering and Biotechnology, 2020)
This work probes the binding kinetics of COOH-terminus of Clostridium perfringens enterotoxin (c-CPE) and claudin expressing MCF-7 cells using force spectroscopy with optical tweezers. c-CPE is of high biomedical interest due to its ability to specifically bind to claudin with high affinity as well as reversibly disrupt tight junctions whilst maintaining cell viability. We observed single-step rupture events between silica particles functionalized with c-CPE and MCF-7 cells. Extensive calibration of the optical tweezers’ trap stiffness and displacement of the particle from trap center extracted a probable bond rupture force of ≈ 18 pN. The probability of rupture events with c-CPE functionalized silica particles increased by 50 % compared to unfunctionalized particles. Additionally, rupture events were not observed when probing cells not expressing claudin with c-CPE coated particles. Overall, this work demonstrates that optical tweezers are invaluable tools to probe ligand-receptor interactions and their potential to study dynamic molecular events in drug-binding scenarios.